Scale of Death Anxiety (SDA): Development and Validation - Cai, Wei; Tang, Yung-lung; Wu, Song; Li, Hong (Frontiers in Psychology, 2017)
This study developed and validated a new measure to assess the death anxiety (i.e., Scale of Death Anxiety, SDA) on an individual’s somatic, cognitive, emotional, and behavioral reactions from a symptomatic perspective in Chinese youth samples. Following a systematic process, a four-factor structure of the SDA was identified through principle components analysis and confirmatory factor analysis that revealed four aspects of death anxiety: Dysphoria, Death Intrusion, Fear of Death, and Avoidance of Death. The results of this study indicate that the SDA has a clear factor structure and good psychometric properties. The SDA supports death anxiety as a multidimensional construct, and the foundational role of fear of death in the generation of death anxiety. This scale is valuable and beneficial to research on death anxiety. This study makes a significant contribution to the literature because the SDA is the first assessment of death anxiety to include the constructs of dysphoria and somatic symptoms. And the potential clinical practice of the SDA was discussed.